Afternoon on the amazon ebook - Osborne, Mary Pope (Magic Tree House, 2010)
The #1 bestselling chapter book series of all time celebrates 25 years with new covers and a new, easy-to-use numbering system! Vampire bats and killer ants? That's what Jack and Annie are about to run into when the Magic Tree House whisks them away to the Amazon River. It's not long before they get hopelessly lost. Will they be able to find their way back to the tree house? Or are Jack and Annie stuck forever in the rain forest? Did you know that there’s a Magic Tree House book for every kid? Magic Tree House: Adventures with Jack and Annie, perfect for readers who are just beginning chapter books Merlin Missions: More challenging adventures for the experienced reader Super Edition: A longer and more dangerous adventure Fact Trackers: Nonfiction companions to your favorite Magic Tree House adventures